1980
DOI: 10.1063/1.439489
|View full text |Cite
|
Sign up to set email alerts
|

Solvation forces in simple dense fluids. I

Abstract: The grand canonical ensemble Monte Carlo method is used to calculate the density profile of a simple dense liquid, under conditions close to the vapor line, between two solid bodies and also the solvation force between the solids due to the simple fluid. The force is large compared with the van der Waals force at moderate surface separations, h, but is an oscillatory function of h. At small values of h the solvation force is strongly repulsive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(165 citation statements)
references
References 23 publications
8
157
0
Order By: Relevance
“…Confined lubricants behave very differently to their bulk counterparts under shear, and density inhomogeneity can lead to the breakdown of continuum approximations such as Navier-Stokes hydrodynamics [133]. Density oscillations in confined fluids were first identified in Monte−Carlo (MC) simulations of L−J liquids [65,134]. Shortly afterwards, surface forces apparatus (SFA) experiments by Horn and Israelachvili on confined octamethylcyclotetrasiloxane (OMCTS) [135] (a quasi-spherical molecule) showed that the force between two surfaces does not evolve smoothly with the separation distance as predicted by the van der Waals theory.…”
Section: Confined Nemd Simulations Of Liquid Lubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confined lubricants behave very differently to their bulk counterparts under shear, and density inhomogeneity can lead to the breakdown of continuum approximations such as Navier-Stokes hydrodynamics [133]. Density oscillations in confined fluids were first identified in Monte−Carlo (MC) simulations of L−J liquids [65,134]. Shortly afterwards, surface forces apparatus (SFA) experiments by Horn and Israelachvili on confined octamethylcyclotetrasiloxane (OMCTS) [135] (a quasi-spherical molecule) showed that the force between two surfaces does not evolve smoothly with the separation distance as predicted by the van der Waals theory.…”
Section: Confined Nemd Simulations Of Liquid Lubricantsmentioning
confidence: 99%
“…This technique was developed from GCEMC (grandcanonical ensemble Monte Carlo) [65] to investigate interesting results from surface force apparatus (SFA) experiments of confined liquid films [66]. In GCMD simulations, a reservoir of fluid molecules surrounds the confined system [64], thus allowing molecules to be "squeezed out" from between the solid surfaces in one or more directions at high pressure [67].…”
Section: Temperature and Pressure Controlmentioning
confidence: 99%
“…It is induced by the sharp cutoff in fluid density at the wall and the pair correlation function g(r) between fluid atoms (Abraham, 1978;Toxvaerd, 1981;Nordholm and Haymet, 1980;Snook and van Megen, 1980;Plischke and Henderson, 1986). An initial fluid layer forms at the preferred wall-fluid spacing.…”
Section: A Flow Boundary Conditionsmentioning
confidence: 99%
“…Theoretical work and computer simulations of Lennard-Jones fluids and hard spheres show that the oscillatory solvation force originates from the stratification or ordering of the molecules in layers when the fluid is confined by the surfaces [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%